Liberty, property and popular politics England and Scotland, 1688-1815 : essays in Honour of H.T. Dickinson - Pentland, Gordon; Davis, Michael T. 1969- (Edinburgh University Press, 2016)
This collection (in honour of an internationally-renowned scholar who had shaped both scholarly and popular understandings of the period) comprises fourteen chapters written by specialists in the period and provides an appealing and illuminating cross-section of current research